Factor VIII levels in non-severe hemophilia A - Krassova, Snejana (Henry Stewart Talks, 2024)
Non-severe hemophilia, Types of bleeds in hemophilia, Hemophilic arthropathy, Bleed rates and treatments, Joint disease, Impact of hemophilia on lifestyle, Prophylaxis, Case studies to treat non-severe hemophilia